Molecular detection of Bartonella spp. and Rickettsia spp. in bat ectoparasites in Brazil - Do Amaral, Renan Bressianini [UNESP]; Lourenço, Elizabete Captivo; Famadas, Kátia Maria; Garcia, Amanda Barbosa [UNESP]; Machado, Rosangela Zacarias [UNESP]; André, Marcos Rogério [UNESP] (Public Library of Science (PLoS), 2018)
The family Streblidae comprises a monophyletic group of Hippoboscoidea, hematophagous dipterans that parasitize bats. Bartonella spp. and Rickettsia spp. have been reported in bats sampled in Europe, Africa, Asia, North, Central and South America. However, there are few reports on the Bartonella and Rickettsia bacteria infecting Hippoboscoidea flies and mites. While Spinturnicidae mites are ectoparasites found only in bats, those belonging to the family Macronyssidae comprise mites that also parasitize other mammal species. This study investigates the occurrence and assesses the phylogenetic positioning of Bartonella spp. and Rickettsia spp. found in Streblidae flies and Spinturnicidae and Macronyssidae mites collected from bats captured in Brazil. From May 2011 to April 2012 and September 2013 to December 2014, 400 Streblidae flies, 100 Macronyssidaes, and 100 Spinturnicidae mites were collected from bats captured in two sites in northeastern Nova Iguaçu, Rio de Janeiro, southeastern Brazil. Forty (19.8%) out of 202 Streblidae flies were positive for Bartonella spp. in qPCR assays based on the nuoG gene. Among the flies positive for the bacterium, six (18%) were Paratrichobius longicrus, seven (29%) Strebla guajiro, two (40%) Aspidoptera phyllostomatis, five (11%) Aspidoptera falcata, one (10%) Trichobius anducei, one (25%) Megistopoda aranea, and 18 (32%) Trichobius joblingi, and collected from bats of the following species: Artibeus lituratus, Carollia perspicillata, Artibeus planirostris, Sturnira lilium, and Artibeus obscurus. Six sequences were obtained for Bartonella (nuoG [n = 2], gltA [n = 2], rpoB [n = 1], ribC = 1]). The phylogenetic analysis based on gltA (750pb) gene showed that the Bartonella sequences clustered with Bartonella genotypes detected in bats and ectoparasites previously sampled in Latin America, including Brazil. Only one sample (0.49%) of the species Trichobius joblingi collected from a specimen of Carollia perspicillata was positive for Rickettsia sp. in cPCR based on the gltA gene (401bp). This sequence was clustered with a ‘Candidatus Rickettsia andaenae genotype detected in an Amblyomma parvum tick collected from a rodent in the southern region of Brazilian Pantanal. The sampled Macronyssidae and Spinturnicidae mites were negative for Bartonella spp. and Rickettsia spp. This study demonstrated the first occurrence of Bartonella spp. and Rickettsia spp. DNA in Streblidae flies collected from bats in Brazil.